PEMBINAAN DAN PENGAWASAN DALAM PENGGUNAAN DANA DESA DI KECAMATAN SIAK KABUPATEN SIAK TAHUN 2017 - Musfita Armala Sari; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Village funds are a budget intended for villages to finance the government administration, development, community empowerment and community development. Village funds are the highest source of village income. Theerefore, guidance and supervision in the use of village funds in mandatory for local governments so that the target of village funds can be achieved, that are adequate development and independent community. The research aims to describe (1) the form of guidance and supervision carried out by the community and village empowerment and the government of Siak Sub-district and Inspectorate of Siak District, and (2) describe the inhibiting factors in the use of village funds in Siak Sub-district of Siak District in 2017.The result of the research show that guidance and supervision are carried out through several stages, namely pre-distribution stage, distribution stage, and post-distribution stage. The guidance and supervision in the use of village funds lies in the stages of palling and use, but n empirical conditions they are not implemented. Furthermore, supervision lies in all stages including the stages of planning, budgeting, distributing, using, reporting and accountability. However, only three stages are implemented. The inhibiting factors in guidance and supervision in the use of village funds are the delays in the implementation of data verification, lack of coordination with village facilitators and lack of time for supervision by Siak District Inspektorate. Guidance and supervision in the use of village funds in SIak District have not been implemented optimally, because until now there are still several aspects of it that have not yet been implemented and there are still several inhibiting factors in guidance and supervision in the use of village funds of Siak District.  Keywords : Guidance, Supervision, Village Funds